Understanding the antecedents of knowledge sharing behaviour and its relationship to team effectiveness and individual learning - Lin, Chun-Yu; Huang, Chung-Kai (Australasian Journal of Educational Technology, 2020)
Due to the competitive and rapidly changing nature of the external business environment, university students must acquire the ability to cooperate, share knowledge, and enhance team effectiveness and learning in the workplaces of the future. Consequently, the design of business courses in higher education merits further discussion. Based on the notions of team-based learning and flipped classrooms, we proposed a business course model that consisted of three main phases: before-class, in-class, and after-class online course activities. After implementing the course models in two business courses at two public universities in Taiwan, a survey based on social learning and social exchange theories was distributed. The data collected from 218 undergraduate business students were analysed. The findings reveal that value in team members’ contributions is positively associated with team trust and each has a significant impact on knowledge sharing and team effectiveness. Knowledge sharing played a key role in this learning context and was a significant mediator between perceptions of value in team members’ contributions and team effectiveness, as well as between team trust and team effectiveness. In addition, team effectiveness was a benefit to individual learning in these classes.